(untitled) (Al-Academy, 2023)
As a result of the developments that occurred in technological and digital technologies, which had a fundamental role in changing the paths of science, including the sciences of communication and the art of design, especially since these developments were the result of the information revolution, which called for the need to find alternatives that contribute to organizing presentations of information and texts in accordance with the manufacture of constructive content to deliver A communication message for the recipient to achieve culture and communication together, as it has become necessary to employ technical and digital developments in organizing that information according to the rules and laws of design and producing newspapers associated with infographic technology, from which the visual representation of the communication message is embodied in its abbreviated form, and since this technology contributes greatly to the transformation of complex and confusing information Perceptions of receiving turn into simplified information that has the ability to penetrate the thought of receiving away from confusion, so the researcher raises the following question: What is the communication effectiveness of designing and producing digital newspapers associated with infographics?The second chapter (theoretical framework) included the first topic: the communicative effectiveness of design and digital output. And the second topic: infographics and its employment associations in the designs of digital newspapers, while the third chapter (research procedures and methodology) determines the selection of the research community and the samples subject to analysis according to the analysis form that was built according to the indicators of the theoretical framework, and finally the fourth chapter is devoted to reviewing the results produced by the analysis, the most important of which The couplings and partnerships achieved between graphic and infographic design, which represents one of the most important branches of design, resulted in providing various formal representations that carry values and functional, aesthetic and communicative connotations of multiple data and trends that included all samples. As for the conclusions, it was based on the fact that infographics have an effective role in simplifying the informational content associated with the laws of visual design, especially since these associations will contribute effectively to increasing the effectiveness of communication. Despite this importance, the infographics in newspaper designs are still weak and ineffective